Modern legal aspects and the role of a psychologist in the treatment of chronic pain - Savchuk, Вікторія (Psychosomatic Medicine and General Practice, 2021)
This text is the conference abstract to the materials of the poster report to the IV scientific-practical conference with international participation "Psychosomatic medicine: science and practice". It is dedicated to the modern legal aspects and the role of a psychologist in the treatment of chronic pain.